Enterprise Resource Planning using Sentiment Examination - K, Deepthi; Mathapati, Abhishek (International journal of recent technology and engineering, 2019)
Enterprise Resource Planning(ERP) is a successful implementation to simplify the business process. The ERP system is an digitalized process of the company from manual updating to automated update.ERP system is a web-application that can be used by all the employees from anywhere and anytime where the data is stored in the centralized database and also ERP is used to assign the task to the particular user automatically based on reviews provided. The application mainly have 4 types of users namely Admin, Telecaller, Marketer and Developer. The admin has the authority to add employees, assign the roles and also has access to view all the information updated by different employee of the organization. The Telecaller will make calls to the client to fix the meeting and update the information in the application such as Name, address, meeting date etc. This information is visible to the marketer who will be meeting the client on the fixed date and discuss about the project. The marketer then update the status about the meeting in the application along with the client review. Based on client review, naïve bayes algorithm is used to classify the review into positive and negative review. If the review is positive then the project is directly assigned to the developer else if the review is negative the status is updated to the admin so that the admin can provide proposals or can fix meeting again for client satisfaction and confirmation. After developer get assigned to project, developer starts the project and send demo to the admin. The approval of the demo is done by admin then the developer completes the project and hosts the particular project. By this system the goal of digitalization and assigning the task to the employees automatically can be achieved.